Changing in Spatial and Temporal Accumulation of Microplastics in the Water Column at Urban Ko Yo Community in Songkhla Lagoon, Thailand - Rodcharoen, Eknarin; Pat-Iam, Sakarat; Chotikarn, Ponlachart; Sinutok, Sutinee; Wichachucherd, Bongkot (Trends in Sciences, 2024)
Ko Yo, situated at the mouth of Songkhla Lagoon, is an urban ecosystem renowned as one of the active areas of Songkhla Province. Numerous anthropogenic activities occur in this area, including homestay tourism, aquaculture, fishing, and the operation of restaurants, all of which generate significant environmental waste. Microplastics represent a widespread pollutant and have been widely recognized as a critical environmental concern. However, they have received little attention among the general public. Therefore, this study investigated the type and quantity of microplastic accumulation in the water bodies surrounding Ko Yo, Songkhla Province. Water sampling stations were established along the coastline and 1 km into the subtidal area, and sampling was conducted for a year. Microplastics in the water samples were recorded and categorized using a modified size and color sorting protocol. Samples were analyzed via Fourier-transform infrared spectroscopy to identify microplastic polymers. The results revealed the accumulation of 6 types of microplastics around Ko Yo: Cotton polyester blend, polyester, alkyd, polypropylene, polyvinylchloride, and low-density polyethylene. These polymers most frequently occurred during the summer and the northeastern monsoon season. Cotton polyester blend, a synthetic fiber commonly used in clothing, furniture, ropes, nets, and cages, was found in the highest quantities across all months and stations. This update on microplastic contamination in natural environments near household areas could lead the idea of the microplastic status around Ko Yo and provide vital insights into the environmental and health implications of microplastics. HIGHLIGHTS Ko Yo is an urban ecosystem and high anthropogenic activities of Songkhla Province. This research concerned on the microplastic pollution along Ko Yo. Water sampling stations were established along the coastline and 1 km into the subtidal area, and sampling was conducted for a year. Six types of microplastics found in water around Ko Yo: Cotton polyester blend, polyester, alkyd, polypropylene, polyvinylchloride, and low-density polyethylene. These polymers most frequently occurred during the summer and the northeastern monsoon season. Cotton polyester blend, a synthetic fiber commonly used in clothing, furniture, ropes, nets, and cages, was found in the highest quantities across all months and stations. GRAPHICAL ABSTRACT